A super-tough PC / PBT alloy and its preparation method and application

By using composite toughening agents to form elastomer balls in super toughening PC/PBT alloys, the problem of high production costs in the prior art is solved, and the effects of high ductility and high notch impact strength are achieved. It is suitable for safety helmet shell materials.

CN119735923APending Publication Date: 2025-04-01NINGBO HUATENG SHOUYAN NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411049199.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-01
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

When improving toughness, existing ultra-tough PC/PBT alloys need to increase the use of organic toughening agents, resulting in excessive production costs.

Method used

A composite toughening agent is introduced into the PC/PBT alloy, and elastomer balls are formed through melt extrusion, reducing the use of organic toughening agent and improving the toughness of the alloy.

Benefits of technology

It realizes that while reducing the amount of organic toughening agent used, it improves the toughness and ductility of PC/PBT alloys, reduces production costs, and meets the material performance requirements in the field of safety helmet shells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735923A_ABST
    Figure CN119735923A_ABST
Patent Text Reader

Abstract

The present invention relates to a super-tough PC / PBT alloy and a preparation method and application thereof. The super-tough PC / PBT alloy provided by the present invention comprises polycarbonate resin, polybutylene terephthalate resin, composite toughening agent, antioxidant, and lubricant. The composite toughening agent is melt-extruded in the super-tough PC / PBT alloy to form elastomeric spheres, and the composite toughening agent is composed of 20 to 95 wt% of toughening agent A, 3 to 30 wt% of toughening agent B, and 0.1 to 2 wt% of coupling agent C. The present invention adopts inorganic micro-nanoparticles as synergistic toughening agents to improve the toughening efficiency. While reducing the use amount of organic toughening agents, it reduces the proportion of PC resin in PC / PBT alloys, saves production costs, and provides huge benefits for enterprises to reduce costs and increase efficiency. The super-tough PC / PBT alloy provided by the present invention has excellent ductility and high notch impact strength, and can meet the performance requirements of materials in the field of safety helmet shells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and particularly relates to a super-tough PC / PBT alloy and a preparation method and application thereof. Background Art

[0002] Polycarbonate (PC) is an amorphous material with good toughness for thin products, while polybutylene terephthalate (PBT) is a semi-crystalline material. Since it contains crystalline regions that can improve its ability to resist chemical corrosion, the two can complement each other after blending. Blending and modifying PC and PBT can overcome the shortcomings of poor heat resistance, low impact resistance, and low notched impact strength, while making up for the deficiencies in chemical resistance, molding processability, and wear resistance. In order to further broaden the application scope of PC / PBT alloys, more and more attention is currently being paid to the new material of super-tough PC / PBT alloys.

[0003] Major companies have conducted in-depth research on super-tough PC / PBT alloys and developed a series of modification methods for super-tough PC / PBT alloys. However, these methods mainly focus on increasing the proportion of polycarbonate in the two-phase alloy. For example, in Chinese patent CN115895229A, polycarbonate requires 40 to 60 parts (polybutylene terephthalate 15 to 40 parts), and in Chinese patent CN104710743A, PC accounts for 40 to 60% (PBT accounts for 20 to 40%). Or the toughness of PC / PBT alloys can be improved by increasing the content of toughening agents. For example, Wei Gang (Mechanical Properties and Submicron Phases of PBT / PC / E-MA-GMA Ternary Blends [J]) et al. studied the effect of E-MA-GMA on improving the impact properties of PC / PBT alloys. When PBT / PC = 50 / 50 (mass ratio) and the mass fraction of E-MA-GMA is 10%, the notched impact strength can reach 93kJ / m 2 . For example, in Chinese patent CN104231568B, 10 to 25 parts of toughening agent need to be added to achieve the super-tough effect of PC / PBT alloy. On the whole, the toughening agents selected are organic toughening agents with good compatibility with PC and PBT resin matrices, such as POE-g-GMA, GMA, MBS, etc. However, the toughening efficiency of these organic toughening agents is generally not high, and more than 10 parts need to be added to achieve the super-tough effect of PC / PBT alloy. Achieving super-tough effect by increasing the proportion of PC in PC / PBT alloy or by increasing the content of toughening agent will result in excessively high production costs for enterprises. Summary of the invention

[0004] The present invention aims to provide an ultra-tough PC / PBT alloy with high ductility and high notch impact strength that can be applied to the field of safety helmet shells and a preparation method thereof, so as to overcome the defect of high production cost in the prior art. The present invention adds a composite toughening agent to the PC / PBT alloy, and the composite toughening agent can form "elastic ball" in the resin matrix, thereby reducing the amount of organic toughening agent used and improving the toughness of PC / PBT.

[0005] One of the purposes of the present invention is to provide a super-tough PC / PBT alloy, comprising a polycarbonate resin, a polybutylene terephthalate resin, a composite toughening agent, an antioxidant, and a lubricant, wherein the composite toughening agent is melt-extruded to form elastomer beads in the super-tough PC / PBT alloy.

[0006] According to the present invention, in the super-tough PC / PBT alloy:

[0007] The composite toughening agent is melt-extruded to form elastic beads with a particle size of 10nm to 80μm, preferably 50nm to 10μm;

[0008] The composite toughening agent comprises toughening agent A, toughening agent B and coupling agent C;

[0009] Wherein, the toughening agent A is selected from at least one polymer containing an acrylic acid ester monomer, preferably at least one selected from a terpolymer of methyl methacrylate-butadiene-styrene, a binary or ternary copolymer formed by an ethylene monomer and an acrylic acid ester monomer and / or a glyceryl acrylate monomer, and glycidyl methacrylate; the acrylic acid ester monomer is selected from at least one of methyl acrylate, butyl acrylate, ethyl acrylate, and methyl methacrylate; the glyceryl acrylate monomer is selected from at least one of glycidyl acrylate and glycidyl methacrylate;

[0010] The toughening agent B is selected from micro-nano inorganic compounds, preferably at least one of calcium carbonate, barium sulfate, silicon dioxide, zinc oxide, zirconium phosphate, and zirconium oxide with micro-nano size; the particle size of the toughening agent B is 1nm to 100μm, preferably 10nm to 60μm;

[0011] The coupling agent C is selected from at least one of aluminate coupling agents, silane coupling agents, borate coupling agents, titanate coupling agents, boroaluminate coupling agents, borotitanate coupling agents, and titanate coupling agents, preferably at least one of silane coupling agents, aluminate coupling agents, and titanate coupling agents. In the present invention, the silane coupling agent, aluminate coupling agent, and titanate coupling agent are not particularly limited, and existing commercially available coupling agent products or coupling agents obtained according to the preparation methods known in the prior art can be used.

[0012] The present invention selects suitable inorganic micro-nanoparticles as synergistic toughening agents, thereby increasing the surface free energy of the composite toughening agent and reducing the compatibility of the composite toughening agent with the resin matrix (PC and PBT), so that the composite toughening agent can form "elastic ball" in the resin matrix, thereby reducing the usage of the organic toughening agent and improving the toughening efficiency.

[0013] According to the present invention, in the super-tough PC / PBT alloy, based on the total weight of the composite toughening agent as 100wt%, the toughening agent A is 20-95wt%, the toughening agent B is 3-30wt%, and the coupling agent C is 0.1-2wt%; preferably, based on the total weight of the composite toughening agent as 100wt%, the toughening agent A is 40-90wt%, the toughening agent B is 10-30wt%, and the coupling agent C is 0.1-1wt%.

[0014] According to the present invention, in the super-tough PC / PBT alloy:

[0015] The antioxidant is not particularly limited, and commonly used antioxidants can be used. Specifically, the antioxidant includes but is not limited to at least one of hindered phenol antioxidants and phosphite antioxidants. For example, at least one of antioxidant 1010, antioxidant 1098, antioxidant 626, and antioxidant 168 can be used.

[0016] The lubricant is selected from at least one of rice bran wax, montan acid wax, calcium stearate and zinc stearate;

[0017] Based on the total weight of the super-tough PC / PBT alloy as 100wt%, the polycarbonate resin is 5-45wt%, the polybutylene terephthalate resin is 30-80wt%, the composite toughening agent is 0.5-5wt%, the antioxidant is 0.1-2wt%, and the lubricant is 0.1-2wt%; preferably, based on the total weight of the super-tough PC / PBT alloy as 100wt%, the polycarbonate resin is 10-40wt%, the polybutylene terephthalate resin is 40-70wt%, the composite toughening agent is 1-3wt%, the antioxidant is 0.1-1wt%, and the lubricant is 0.1-1wt%.

[0018] The second object of the present invention is to provide a method for preparing the above-mentioned super-tough PC / PBT alloy, comprising: mixing components including the polycarbonate resin, polybutylene terephthalate resin, composite toughening agent, antioxidant, and lubricant to obtain the super-tough PC / PBT alloy.

[0019] According to the present invention, the preparation method of the super-tough PC / PBT alloy specifically comprises:

[0020] (1) Preparation of composite toughening agent

[0021] Adding components including toughening agent A, toughening agent B and coupling agent C into a high-speed mixer, and mixing and stirring to obtain a composite toughening agent;

[0022] (2) Preparation of super-tough PC / PBT

[0023] The components including polycarbonate resin, polybutylene terephthalate resin, the composite toughening agent obtained in step (1), antioxidant, and lubricant are mixed at high speed and then melt-extruded to obtain the super-tough PC / PBT alloy.

[0024] Specifically, in the preparation method of the super-tough PC / PBT alloy:

[0025] The toughening agent A, toughening agent B and coupling agent C in step (1) can be mixed by high-speed stirring at room temperature using a commonly used high-speed stirrer. The specific conditions of high-speed stirring are not particularly limited, and the toughening agent A, toughening agent B and coupling agent C can be fully mixed. For example, the mixing and stirring time is 5 to 10 minutes;

[0026] The melt extrusion in step (2) is preferably carried out in a twin-screw extruder; the conditions for melt extrusion are not particularly limited, and the melt extrusion conditions commonly used in the art can be commonly used; preferably, the process conditions for melt extrusion are: the temperature of each section of the twin-screw extruder is controlled between 220 and 240°C, and the screw speed is 280 to 350 rpm.

[0027] The third object of the present invention is to provide a super-tough PC / PBT alloy obtained by the above preparation method, which has a tensile strength of 50-80 MPa, an elongation at break of 130-180%, a flexural strength of 70-90 MPa, a flexural modulus of 1800-2300 MPa, and a notched impact strength of 100-130 KJ / m 2 .

[0028] A fourth object of the present invention is to provide a super-tough PC / PBT alloy that can be used as an impact-resistant safety material, for example, as a safety helmet shell material.

[0029] Compared with the prior art, the present invention improves the surface free energy of the composite toughening agent by selecting suitable inorganic micro-nanoparticles as synergistic toughening agents, reduces the compatibility of the composite toughening agent with the resin matrix (PC and PBT), enables the composite toughening agent to form "elastic body balls" in the resin matrix, improves the toughening efficiency, and reduces the use amount of organic toughening agents while also reducing the proportion of PC resin in the PC / PBT alloy, saving production costs and providing huge benefits to enterprises in reducing costs and increasing efficiency. The PC / PBT alloy provided by the present invention has excellent ductility and high notch impact strength, can meet the performance requirements of materials in the field of safety helmet shells, and is a relatively ideal material in the field of safety helmet shells.

[0030] Beneficial effects of the present invention:

[0031] (1) The present invention reduces the proportion of PC in the PC / PBT alloy, thereby reducing the production cost while retaining the respective advantages of PC and PBT resins;

[0032] (2) The present invention uses inorganic micro-nanoparticles as synergistic toughening agents, which increases the surface free energy of the composite toughening agent, reduces the compatibility of the composite toughening agent with the resin matrix (PC and PBT), and enables the composite toughening agent to form "elastic ball" in the resin matrix, thereby increasing the toughening efficiency, reducing the amount of organic toughening agent used, and reducing the production cost;

[0033] (3) The process flow of the present invention is simple, the operation is simple, and it is easy to realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a SEM image of the super-tough PC / PBT alloy obtained in Example 1;

[0035] Figure 2 This is the SEM image of the PC / PBT alloy obtained in Comparative Example 1;

[0036] Figure 3 This is the SEM image of the PC / PBT alloy obtained in Comparative Example 2. DETAILED DESCRIPTION

[0037] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0038] In order to better understand the present invention, the present invention is further described below in conjunction with examples. The following examples are only intended to illustrate the present invention rather than to limit it.

[0039] According to an embodiment of the present invention, the super-tough PC / PBT alloy is prepared by melt-extruding components including polycarbonate resin (PC), polybutylene terephthalate resin (PBT), composite toughening agent, antioxidant, and lubricant. In the melt-extrusion process, the composite toughening agent forms elastomeric spheres uniformly dispersed in the super-tough PC / PBT alloy material, thereby improving the toughness of the PC / PBT alloy material.

[0040] According to an embodiment of the present invention, the composite toughening agent comprises a toughening agent A, a toughening agent B and a coupling agent C. The toughening agent A is selected from at least one polymer containing an acrylic acid ester monomer, preferably at least one of a terpolymer of methyl methacrylate-butadiene-styrene, a binary or ternary copolymer formed by an ethylene monomer and an acrylic acid ester monomer and / or a glyceryl acrylate monomer, and glycidyl methacrylate; the acrylic acid ester monomer is selected from at least one of methyl acrylate, butyl acrylate, ethyl acrylate, and methyl methacrylate; the glyceryl acrylate monomer is selected from at least one of glycidyl acrylate and glycidyl methacrylate. The toughening agent B is selected from micro-nano inorganic compounds, preferably at least one of calcium carbonate, barium sulfate, silicon dioxide, zinc oxide, zirconium phosphate, and zirconium oxide with micro-nano size; the particle size of the toughening agent B is 1 nm to 100 μm, preferably 10 nm to 60 μm. The coupling agent C is selected from at least one of aluminate coupling agents, silane coupling agents, borate coupling agents, titanate coupling agents, boroaluminate coupling agents, borotitanate coupling agents, and titanate coupling agents, preferably at least one of silane coupling agents, aluminate coupling agents, and titanate coupling agents. In the present invention, the toughening agent A, the toughening agent B, and the coupling agent C can all be prepared using existing commercial products or according to a preparation method known in the prior art.

[0041] According to an embodiment of the present invention, in the super-tough PC / PBT alloy:

[0042] The antioxidant is not particularly limited, and commonly used antioxidants can be used. Specifically, the antioxidant includes but is not limited to at least one of hindered phenol antioxidants and phosphite antioxidants. For example, at least one of antioxidant 1010, antioxidant 1098, antioxidant 626, and antioxidant 168 can be used.

[0043] The lubricant is selected from at least one of rice bran wax, montan acid wax, calcium stearate and zinc stearate;

[0044] Based on the total weight of the super-tough PC / PBT alloy as 100wt%, the polycarbonate resin is 5-45wt%, the polybutylene terephthalate resin is 30-80wt%, the composite toughening agent is 0.5-5wt%, the antioxidant is 0.1-2wt%, and the lubricant is 0.1-2wt%; preferably, based on the total weight of the super-tough PC / PBT alloy as 100wt%, the polycarbonate resin is 10-40wt%, the polybutylene terephthalate resin is 40-70wt%, the composite toughening agent is 1-3wt%, the antioxidant is 0.1-1wt%, and the lubricant is 0.1-1wt%.

[0045] According to an embodiment of the present invention, the preparation method of the super-tough PC / PBT alloy comprises the following specific steps:

[0046] (1) Preparation of composite toughening agent

[0047] Add toughening agent A, toughening agent B and coupling agent C into a high-speed mixer respectively, and stir for 5 to 10 minutes to obtain a composite toughening agent.

[0048] (2) Preparation of super-tough PC / PBT alloy

[0049] PC resin, PBT resin, antioxidant, lubricant and composite toughening agent are stirred and mixed at high speed, and then fed into a twin-screw extruder by a precision-metered feeder for plasticization, melting and compounding. Finally, super-tough PC / PBT alloy can be prepared by extrusion, drawing, cooling, pelletizing and drying.

[0050] The PC / PBT alloy materials prepared in the examples and comparative examples were tested for performance according to ISO standards:

[0051] Tensile properties are tested according to ISO 527;

[0052] Bending properties are tested according to ISO 178;

[0053] Notched impact properties were tested according to ISO 179 / 1eA.

[0054] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0055] Embodiment and comparative example:

[0056] This embodiment is used to illustrate the super-tough PC / PBT alloy and its preparation according to the present invention.

[0057] Example 1

[0058] The super-tough PC / PBT alloy of this embodiment has the following components in percentage by mass: PC is 40%, PBT is 56.5%, a compound of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1 is 0.3%, calcium stearate is 0.2%, and a composite toughening agent is 3%. Among them, the toughening agent A in the composite toughening agent is a terpolymer of methyl methacrylate, butadiene, and styrene (MBS), accounting for 80%, the toughening agent B is nano-calcium carbonate, accounting for 19%, and the particle size of the nano-calcium carbonate is 50-100nm, and the coupling agent is a silane coupling agent KH550, accounting for 1%.

[0059] The preparation process of the super-tough PC / PBT alloy comprises the following specific steps:

[0060] A) Preparation of composite toughening agent:

[0061] Add toughening agent A, toughening agent B and coupling agent C into a high-speed mixer respectively, and stir for 10 minutes to obtain a composite toughening agent;

[0062] B) Preparation of super tough PC / PBT alloy:

[0063] PC resin, PBT resin, antioxidant, lubricant and composite toughening agent were mixed with high-speed stirring, and then fed into a twin-screw extruder (the temperature of each screw section was controlled between 220 and 230°C, and the screw speed was 300 rpm) by a precision metering feeder for plasticization, melting, compounding, and finally extrusion, drawing, cooling, pelletizing, drying, and testing. The performance test results are shown in Table 1.

[0064] Example 2

[0065] The super-tough PC / PBT alloy of this embodiment has the following components in percentage by mass: PC is 37%, PBT is 60%, a compound of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1 is 0.3%, rice bran wax is 0.2%, and a composite toughening agent is 2.5%. Among them, the toughening agent A in the composite toughening agent is ethylene-butyl acrylate-glycidyl methacrylate copolymer (PTW), accounting for 75%, the toughening agent B is nano-silicon dioxide, accounting for 24%, and the coupling agent is silane coupling agent KH560, accounting for 1%.

[0066] The preparation process of the super-tough PC / PBT alloy comprises the following specific steps:

[0067] A) Preparation of composite toughening agent:

[0068] Add toughening agent A, toughening agent B and coupling agent C into a high-speed mixer respectively, and stir for 10 minutes to obtain a composite toughening agent;

[0069] B) Preparation of super tough PC / PBT alloy:

[0070] PC resin, PBT resin, antioxidant, lubricant and composite toughening agent were mixed with high-speed stirring, and then fed into a twin-screw extruder (the temperature of each screw section was controlled between 220 and 230°C, and the screw speed was 300 rpm) by a precision metering feeder for plasticization, melting, compounding, and finally extrusion, drawing, cooling, pelletizing, drying, and testing. The performance test results are shown in Table 1.

[0071] Example 3

[0072] The super-tough PC / PBT alloy of this embodiment has the following components in percentage by mass: PC is 30%, PBT is 67.5%, a compound of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1 is 0.3%, sodium stearate is 0.2%, and a composite toughening agent is 2.0%. Among them, the toughening agent A in the composite toughening agent is a random ternary copolymer of ethylene, acrylate and glycidyl methacrylate (AX8900), accounting for 85%, the toughening agent B is nano zirconium phosphate, accounting for 14%, and the coupling agent is an aluminate coupling agent, accounting for 1%.

[0073] The preparation process of the super-tough PC / PBT alloy comprises the following specific steps:

[0074] A) Preparation of composite toughening agent:

[0075] Add toughening agent A, toughening agent B and coupling agent C into a high-speed mixer respectively, and stir for 10 minutes to obtain a composite toughening agent;

[0076] B) Preparation of super tough PC / PBT alloy:

[0077] PC resin, PBT resin, antioxidant, lubricant and composite toughening agent were mixed with high-speed stirring, and then fed into a twin-screw extruder (the temperature of each screw section was controlled between 220 and 230°C, and the screw speed was 300 rpm) by a precision metering feeder for plasticization, melting, compounding, and finally extrusion, drawing, cooling, pelletizing, drying, and testing. The performance test results are shown in Table 1.

[0078] Comparative Example 1

[0079] The PC / PBT alloy of this comparative example has the following components in percentage by mass: 40% PC, 56.5% PBT, 0.3% antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1, 0.2% calcium stearate, 80% toughening agent A is MBS, 19% toughening agent B is nano calcium carbonate, the particle size of the nano calcium carbonate is 50-100 nm, and 1% coupling agent is KH550.

[0080] The preparation process of the PC / PBT alloy comprises the following specific steps:

[0081] PC resin, PBT resin, antioxidant, lubricant, toughening agent A, toughening agent B and coupling agent C were mixed with high-speed stirring, and then fed into a twin-screw extruder (the temperature of each screw section was controlled between 220 and 230°C, and the screw speed was 300 rpm) by a precision metering feeder for plasticization, melting, compounding, and finally extrusion, drawing, cooling, pelletizing, drying, and testing. The performance test results are shown in Table 1.

[0082] Comparative Example 2

[0083] The PC / PBT alloy of this comparative example has the following components in percentage by mass: 40% PC, 56.5% PBT, 0.3% of a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1, 0.2% calcium stearate, and 3% toughening agent MBS.

[0084] The preparation process of the PC / PBT alloy comprises the following specific steps:

[0085] PC resin, PBT resin, antioxidant, lubricant, toughening agent MBS were mixed with high-speed stirring, and then fed into a twin-screw extruder (the temperature of each screw section was controlled between 220 and 230°C, and the screw speed was 300 rpm) by a precision metering feeder for plasticization, melting, compounding, and finally extrusion, drawing, cooling, pelletizing, drying, and testing. The performance test results are shown in Table 1.

[0086] The mechanical properties of PC / PBT alloys measured in Examples 1 to 3 and Comparative Examples 1 to 2 are shown in Table 1 below:

[0087] Table 1

[0088]

[0089] From the above data comparison, it can be seen that the PC / PBT alloy material prepared by the technical solution provided by the present invention can achieve a super-tough effect and has better ductility.

[0090] from Figures 1 to 3 It can be seen from the SEM image (scanning electron microscope image) that in the super-tough PC / PBT alloy material prepared in Example 1, the composite toughening agent forms "elastomeric balls" in the resin matrix, and the particle size of the elastomer balls is 50nm~10μm, while in Comparative Example 1, the toughening agent component is directly added to the resin material, and no obvious "elastomeric balls" are generated. In Comparative Example 2, only the toughening agent MBS is added, and no obvious "elastomeric balls" are generated.

Claims

1. A super-tough PC / PBT alloy, comprising polycarbonate resin, polybutylene terephthalate resin, composite toughening agent, antioxidant, and lubricant, wherein: The composite toughening agent is melt-extruded to form elastic beads in the super-tough PC / PBT alloy.

2. The super-tough PC / PBT alloy according to claim 1, characterized in that: The particle size of the elastic spheres formed by melt extrusion of the composite toughening agent is 10nm to 80μm, preferably 50nm to 10μm; and / or, The composite toughening agent comprises toughening agent A, toughening agent B and coupling agent C; Wherein, the toughening agent A is selected from at least one polymer containing acrylic ester monomers, preferably at least one selected from methyl methacrylate-butadiene-styrene terpolymer, a binary or ternary copolymer formed by ethylene monomer and acrylic ester monomers and / or glyceryl acrylate monomers, and glycidyl methacrylate; and / or, The toughening agent B is selected from micro-nano inorganic compounds; and / or, The coupling agent C is selected from at least one of aluminate coupling agents, silane coupling agents, borate coupling agents, titanate coupling agents, boroaluminate coupling agents, borotitanate coupling agents, and titanate aluminate coupling agents.

3. The super-tough PC / PBT alloy according to claim 2, characterized in that: In the toughening agent A, the acrylic ester monomer is selected from at least one of methyl acrylate, butyl acrylate, ethyl acrylate and methyl methacrylate; and / or, In the toughening agent A, the glyceryl acrylate monomer is selected from at least one of glycidyl acrylate and glycidyl methacrylate; and / or, The toughening agent B is selected from at least one of calcium carbonate, barium sulfate, silicon dioxide, zinc oxide, zirconium phosphate and zirconium oxide having micro-nano size; and / or, The particle size of the toughening agent B is 1 nm to 100 μm, preferably 10 nm to 60 μm; and / or, The coupling agent C is selected from at least one of a silane coupling agent, an aluminate coupling agent, and a titanate coupling agent.

4. The super-tough PC / PBT alloy according to claim 2, characterized in that: Based on the total weight of the composite toughening agent being 100wt%, the toughening agent A is 20-95wt%, the toughening agent B is 3-30wt%, and the coupling agent C is 0.1-2wt%; Preferably, based on 100 wt% of the total weight of the composite toughening agent, the toughening agent A is 40-90 wt%, the toughening agent B is 10-30 wt%, and the coupling agent C is 0.1-1 wt%.

5. The super-tough PC / PBT alloy according to claim 1, characterized in that: The antioxidant is selected from at least one of hindered phenol antioxidants and phosphite antioxidants; and / or, The lubricant is selected from at least one of rice bran wax, montan acid wax, calcium stearate and zinc stearate.

6. The super-tough PC / PBT alloy according to claim 1, characterized in that: Based on the total weight of the super-tough PC / PBT alloy being 100wt%, the polycarbonate resin is 5-45wt%, the polybutylene terephthalate resin is 30-80wt%, the composite toughening agent is 0.5-5wt%, the antioxidant is 0.1-2wt%, and the lubricant is 0.1-2wt%; Preferably, based on the total weight of the super-tough PC / PBT alloy as 100wt%, the polycarbonate resin is 10-40wt%, the polybutylene terephthalate resin is 40-70wt%, the composite toughening agent is 1-3wt%, the antioxidant is 0.1-1wt%, and the lubricant is 0.1-1wt%.

7. A method for preparing the super-tough PC / PBT alloy according to any one of claims 1 to 6, comprising: The components including the polycarbonate resin, polybutylene terephthalate resin, composite toughening agent, antioxidant and lubricant are mixed to obtain the super-tough PC / PBT alloy.

8. The preparation method according to claim 7, characterized in that: The preparation method specifically comprises: (1) Preparation of composite toughening agent Adding components including toughening agent A, toughening agent B and coupling agent C into a high-speed mixer, and mixing and stirring to obtain a composite toughening agent; (2) Preparation of super-tough PC / PBT alloy The components including polycarbonate resin, polybutylene terephthalate resin, composite toughening agent obtained in step (1), antioxidant and lubricant are stirred and mixed at high speed, and then melt-extruded to obtain the super-tough PC / PBT alloy; wherein the melt extrusion is preferably completed in a twin-screw extruder; more preferably, the process conditions of the melt extrusion are: the screw temperature of each section of the twin-screw extruder is controlled between 220 and 240°C, and the screw speed is 280 to 350 rpm.

9. A super-tough PC / PBT alloy prepared by the preparation method according to any one of claims 7 to 8, wherein the alloy has a tensile strength of 50 to 80 MPa, an elongation at break of 130 to 180%, a flexural strength of 70 to 90 MPa, a flexural modulus of 1800 to 2300 MPa, and a notched impact strength of 100 to 130 KJ / m 2 .

10. The super-tough PC / PBT alloy according to any one of claims 1 to 6 or the super-tough PC / PBT alloy according to claim 9, used as an impact-resistant safety material.

Citation Information

Patent Citations

  • High glow wire high cti super tough flame retardant pbt / pc alloy material and preparation method thereof

    CN104231568B

  • High-strength super-tough PC / PBT composite material and preparation method thereof

    CN104710743A

  • High-heat-resistance super-tough PC / PBT composite material and preparation method thereof

    CN115895229A